Effect of Delaying Onset of Diabetes with a Combination of Case Management and Motivational Interview in Hypertension Patients at Thepha Hospital, Songkhla Province, Thailand - ชายบุญแก้ว, ศุภลักษณ์ (Journal of Health Science of Thailand, 2021)
The purpose of this study was to find out the effect of delaying onset of diabetes with a combination of case management and motivational interviewing in hypertensive patients. It was conducted as a quasiexperimental research with one group post-test design. The samples were 42 hypertension patients selected from purposive sampling. The data were collected during October 2018 to April 2019. All the patients were treated three times per years with case management and motivational interview. Factors affecting insulin resistance of each patient were analyzed, together with information on daily routine activities and laboratory results. They were advised to reduce sedentary lifestyle, to have food for boosting high density lipoprotein and avoid food having low density lipoprotein (LDL), as well as to take Hypolipidemic agent. The data were analyzed using the descriptive statistics of frequency and percentages, comparison mean of FBS with one sample t-test. It was found that after the case management, most patients under the age of 60 years had systolic pressure in level 1 hypertension which increased from 85.7 percent to 95.2 percent. Systolic pressure at the levels 2 and 3 decreased. Triglyceride level of ‹150 mg% increased from 43.9 percent to 87.1 percent, and the level of >150 mg% decreased from 56.1 percent to 12.9 percent. The LDL level of ‹100 mg% increased from 43.9 percent to 45.2 percent, and that of >100 mg% decreased from 57.1 percent to 54.8 percent. For the body mass index (BMI), those with the index of ‹25 kg/m2 decreased from 66.7 percent to 64.4 percent; and the BMI <25 kg/m2 in female patients increased from 33.3 percent to 35.7 percent. The case management approach was found to be significantly effective in delaying the onset of diabetes (with FBS lower than 126 mg/dL) (p<0.001).